Historical Figures and Paradoxical Patterns:: The Quilting Metaphor in Margaret Atwood’s Alias Grace - Murray, Jennifer (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2001)
In a number of Margaret Atwood's works, sewing, knitting, and other forms of handcrafting activities come to be associated with the representation of history, both as a concept and as a narrative account of the past. Alias Grace can be seen as a work of "historiographic metafiction" in which the quilting metaphor participates in the postmodern structures involved in representing a version of the past. Alias Grace points to the paradox that structures historiographic metafiction through the image of the quilt. Atwood interrogates the metaphorical possibilities of the patchwork quilt, which comes to represent the determining paradox of the novel and of historiographic metafiction: that of making present meaning from traces of the past. The handcrafting metaphor can be usefully considered in the context of some of Atwood's earlier works.